Use of daratumumab in a patient with proliferative glomerulonephritis with monoclonal immunoglobulin deposition: A case report. Issue 1 (February 2023) - Doddi, Akshith; Ibrahim, Dalia; Shawwa, Khaled
Monoclonal gammopathy of renal significance (MGRS) is a pathogenic entity associated with significant morbidity, mainly end stage kidney disease. Proliferative glomerulonephritis with monoclonal immunoglobulin deposition (PGNMID), a type of MGRS, is a specific disease resulting from the deposition of a monoclonal immunoglobulin leading to kidney damage. While PGNMID has been recognized to lead to end-stage kidney disease, until recently there was no evidence to guide treatment. Here, we report a case of a patient with PGNMID who responded well to daratumumab.